Personal factors and its association with depression among secondary school children (Bangladesh Journal of Psychiatry, 2018)
Depression is one of the most significant mental health problems among children and adolescents. The objective of the study was to find out the personal factors and its association with depression among secondary school children in two selected schools of Dhaka, Bangladesh. It was a crosssectional study conducted from November 2008 to October 2009 among one boys’ and one girls’ school of Dhaka, Bangladesh. Purposive sampling technique was used to select 144 respondents from class VI to class IX. A self administered semi-structured questionnaire was used to assess the personal factors of children whereas the Center for Epidemiologic Studies Depression Scale for Children (CES-DC) was used to assess their depressive status. The results showed that 13 to 15 years age group constituted the highest proportion which was followed by the age group of 10 to 12 years. There was no significant difference of age of the respondents with or without depression (p>0.05). It was found that girls were two times more likely to have depression than boys. Among all the respondents, 43 students (29.9%) were suffering from depression. Depression was found highest (36.1%) among the respondents of class VIII but no significant association was found between the presence of depression and educational status of the respondents (p>0.05). Depression was found to be proportionately higher among occasional or regular smokers in comparison to those who never smoked. The overall result of the study indicates that possibility of depression is considerably present in school-going children. So, arrangement for the school mental health services is of utmost importance.Bang J Psychiatry June 2016; 30(1): 1-6